THE EFFECT OF OUTDOOR EDUCATION-BASED PHYSICAL FITNESS LEARNING ON ACHIEVEMENT MOTIVATION IN STUDENTS OF STATE SENIOR HIGH SCHOOL 11 MEDAN - Kavita Maharani; Damanik, Suryadi (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to determine the effect of physical fitness learning based on outdoor education on achievement motivation in students of SMA Negeri 11 Medan. This study uses a pretest-posttest control group design. The sampling technique in this study uses a random sampling technique. The sample in the study was 34 students in the experimental class and 34 students in the control class. Data collection was carried out using an achievement motivation questionnaire. Data analysis was carried out using a t-test. The results showed that the t count value> t table (24.868> 2.035). So it can be concluded that there is a significant effect of physical fitness learning based on outdoor education on achievement motivation in students of SMA Negeri 11 Medan. The effect given by physical fitness learning based on outdoor education is also shown by the posttest results (90.17) which are better than the pretest results (75.02) of achievement motivation in students of SMA Negeri 11 Medan.